2014
DOI: 10.1080/03601234.2015.965634
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of thymol or its glucose conjugate, thymol-β-d-glucopyranoside, onCampylobacterin avian gut contents

Abstract: Campylobacter jejuni is an important human food-borne pathogen that can contaminate meat and poultry during processing. Consequently, strategies are sought to reduce the carriage of C. jejuni in food animals before they arrive at the abattoir. Thymol is a natural product that reduces survivability of Campylobacter in vitro, but its rapid absorption from the proximal alimentary tract limits its bactericidal efficacy in vivo. Thymol-β-D-glucopyranoside is more resistant to absorption than free thymol, but its ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
0
17
0
1
Order By: Relevance
“…As another example, David Nisbet's research group (47) investigated the use of a terpene glycoside form compared with the free form of the same terpene. They observed that the glycoside form showed 60 % higher resistance in absorption in pigs (48) and antimicrobial activity in the crops in poultry (49) . Moreover, Hébert et al (50) demonstrated that the microencapsulation of an aldehyde allowed the delivery of a higher dose, avoiding the acute toxic effects of a bolus dose.…”
Section: Practical Aspects Of Botanicals As Feed Additivesmentioning
confidence: 99%
“…As another example, David Nisbet's research group (47) investigated the use of a terpene glycoside form compared with the free form of the same terpene. They observed that the glycoside form showed 60 % higher resistance in absorption in pigs (48) and antimicrobial activity in the crops in poultry (49) . Moreover, Hébert et al (50) demonstrated that the microencapsulation of an aldehyde allowed the delivery of a higher dose, avoiding the acute toxic effects of a bolus dose.…”
Section: Practical Aspects Of Botanicals As Feed Additivesmentioning
confidence: 99%
“…All derivatives are also better antioxidants than the parent compound [ 30 ]. Thymol- β -D-glucopyranoside 25 exhibits anticampylobacter activity ( Figure 8 ) [ 31 ].…”
Section: Monoterpene Monocyclic Derivativesmentioning
confidence: 99%
“…Trials with the antimicrobial phytochemical thymol in small groups of naturally colonized slaughter‐age birds showed a reduction of up to 1.5 log 10 units in Campylobacter counts in the crop, but not ceca, of birds dosed 9 hours previously (Epps et al., ). Similar results were obtained when the conjugate thymol‐β‐ᴅ‐glucopyranoside, which is more stable to foregut digestive processes, was used.…”
Section: Interventions Complementary To Biosecurity and Hygienementioning
confidence: 99%